HUBUNGAN DUKUNGAN KELUARGA DENGAN PEMANFAATAN RUMAH TUNGGU KELAHIRAN - Dessy Hidayati Fajrin (ITKM WIDYA CIPTA HUSADA, 2020)
Birthplace Waiting House is a place or room located near health facility which can be used as temporary dwelling place of pregnant mother and her companion for several days, while waiting for labor to arrive and some Days after delivery. The analytical research design with Cross Sectional approach. Primary data is questionnaire, population is all mothers giving birth in October until Desember 2019 who live in Batulenger District Health Center Sokobanah Subdistrict, Sampang. Independent variable is family support, and Dependenya Variable is Utilization of waiting house of birth. The results were analyzed using Chi Square. Based on the results of research conducted showed that of 54 mothers who did not get family support almost entirely did not utilize the birth house as many as 45 people (60%). And strengthened the result of statistical test of Chi Square with significant level α = 0,05, got result p = 0,000 (α <0,05) mean H0 rejected and Ha accepted. This indicates that there is a relationship between Family Support and the utilization of waiting house.